The German model of corporate governance: Basic features, critical issues, and applicability to transition economies - Peter Nunnenkamp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
The paper briefly sketches alternative models of dealing with principal-agent problems and compares major characteristics of bank-oriented versus marketoriented systems of corporate governance. The ownership structure in Germany is contrasted with evidence for other industrial countries. This forms the basis on which some critical issues of the German model of corporate governance are discussed. The analysis focuses on the role of banks in enterprise control, and on the limits which cross-shareholdings and the system of co-determination may impose on the effectiveness of outsider control. The pros and cons of the German model are evaluated in comparison with alternative systems. Finally, it is discussed whether transition economies are well advised to follow this model rather than market-based systems of corporate control.
Keywords: 330; Eigentümerstruktur; Agency Theory; Bank; Wirtschaftskonzentration; Deutschland